Partnership among firms: Estimating the probability of contact from the Poisson model using repeated Observations - Rosa Bernardini Papalia; Silvia Bertarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
The aim of this paper is to study the probability to find an opportunity of collaboration among small and medium sized firms by participating in the Europartenariat meeting created to encourage co-operation links. Contacts among firms are relatively few in number and are assumed to be generated by a Poisson process. Empirical results of different Poisson regression models with reference to parameters' estimates, predicted probabilities, and marginal effects on event probabilities have been obtained. They provide interesting results related to productive, technological, commercial, and financial projects, in terms of the dynamic behaviour of a typical European firm. Finally, normative evaluation of economic policy has been possible.
Keywords: 330